Perceived helpfulness of caregiver support resources: Results from a state-wide poll - Maija Reblin; Natalie Ambrose; Nina Pastore; Sarah Nowak (Elsevier, 2024)
Objective: Our goal was to identify specific types of services desired by caregivers and determine subgroups most interested in each service type. Methods: Caregiving questions were added to a state-wide poll conducted in a majority-rural state. Those who identified as caregivers (n = 428) were asked to report on the helpfulness of 6 domains of services. Descriptive analysis and logistic regressions were conducted. Results: Top resources caregivers identified as potentially helpful included hands-on services (33.9%), help coordinating care from multiple providers (21.5%), help with finances (18.9%), and help managing emotional stress (17.8%). Only 15% indicated no caregiver resources would be helpful. Younger caregivers endorsed several service domains as more helpful than older caregivers; caregivers reporting higher stress were more likely to endorse most domains as helpful. Conclusion: Data reinforces the overwhelming need to offer caregiver services. Navigation and integrated and tailored service models may be beneficial to help caregivers identify and access appropriate services within healthcare systems. Innovation: This study uses an innovative approach to identifying needs of caregivers, who are often invisible within the healthcare system. Our findings suggest a paradigm shift is needed to broaden the scope and depth of services offered to caregivers.